PERBANDINGAN TEBAL KERABANG, PENURUNAN BERAT TELUR, DAN NILAI HAUGH UNIT TELUR AYAM RAS UMUR SIMPAN SEPULUH HARI DARI STRAIN AYAM YANG BERBEDA - Sakroni ,; Tintin Kurtini; Khaira Nova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The objective of this research was to find out the comparison of ten days old eggs on shell thickness, weight lost, and egg haugh unit value from different layer strains. Layer strains to use in this research were isa brown and lohman brown strains. 50 egg samples were taken from each strain from layerof 58 weeks old. This reserach was conducted in Mulawarman egg chicken farming in Tegal Sari village of GadingRejo sub district, in Pringsewu district, and in Animal Production and Reproduction Laborator, in Animal Husbandry Departement of Agriculture Faculty in Lampung University inApril 2015. Eggs from each strain were stored for ten days. Data were tested by using t-student test with 5% trust level. The result showed that egg weight lost from lohman brown strain was significantly lower (P< 0.05) than isa brown strain, while Haugh Unit and shell thickness from both strains were not significantly different (P>0.05) at ten days storage. Keywords : Shell thickness, egg weight lost,haughunit value, and different layer strains.